European Cohesion Policy: A Proposed Evaluation Model - Alina Bouroşu (Costăchescu) (Romanian Journal of European Affairs, 2012)
The current approach of European Cohesion Policy (ECP) is intended to be a bridge between different fields of study, emphasizing the intersection between “the public policy cycle, theories of new institutionalism and the new public management”. ECP can be viewed as a focal point between putting into practice the principles of the new governance theory, theories of economic convergence and divergence and the governance of common goods. After a short introduction of defining the concepts used, the author discussed on the created image of ECP by applying three different theories, focusing on the structural funds implementation system (SFIS), directing the discussion on the evaluation part of this policy, by proposing a model of performance evaluation of the system, in order to outline key principles for creating effective management mechanisms of ECP.